A new species of Mollinedia (Monimiaceae, Laurales) from Rio de Janeiro state using genomic size estimation as support - Zavatin, Danilo Alvarenga; Peixoto, Ariane Luna; Gentile, Chiara; Evangelista-Silva, Samara; Moraes, Ana Paula; De Lírio, Elton John (Brittonia, 2024)
With ca. 60 species, Mollinedia is the second most diverse genus of Monimiaceae and the richest genus of the family in the Neotropics. In Brazil, the Atlantic Forest is the richest biome for Mollinedia, with 34 species, most of which are endemic to this biome. Here we describe a new species of Mollinedia endemic to Rio de Janeiro state, based partly on molecular evidence.